2015
DOI: 10.1371/journal.pone.0122605
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Identify the Geographic Origin of Dust Samples

Abstract: There is a long history of archaeologists and forensic scientists using pollen found in a dust sample to identify its geographic origin or history. Such palynological approaches have important limitations as they require time-consuming identification of pollen grains, a priori knowledge of plant species distributions, and a sufficient diversity of pollen types to permit spatial or temporal identification. We demonstrate an alternative approach based on DNA sequencing analyses of the fungal diversity found in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 32 publications
5
46
0
Order By: Relevance
“…For example, the results of a study that sequenced fungi from approximately 600 soil samples across North American Pinaceae forests were highly consistent with dispersal limitation (BOX 3), as statistical ordinations showed strong geographical clustering of fungal communities 3 , and community similarity decreased with increasing distance between samples, even after controlling for climate and environment. In fact, the geographical signal of fungal communities in soil is so strong that fungal community composition can be used to identify the origin of dust samples 43 . Although fungal communities overall show strong patterns of regional endemism and dispersal limitation, long-distance dispersal can occur over short timescales through the aerial movement of spores or, over longer timescales, alongside the migration of vegetation during climatic change (see below).…”
Section: Endemismmentioning
confidence: 99%
“…For example, the results of a study that sequenced fungi from approximately 600 soil samples across North American Pinaceae forests were highly consistent with dispersal limitation (BOX 3), as statistical ordinations showed strong geographical clustering of fungal communities 3 , and community similarity decreased with increasing distance between samples, even after controlling for climate and environment. In fact, the geographical signal of fungal communities in soil is so strong that fungal community composition can be used to identify the origin of dust samples 43 . Although fungal communities overall show strong patterns of regional endemism and dispersal limitation, long-distance dispersal can occur over short timescales through the aerial movement of spores or, over longer timescales, alongside the migration of vegetation during climatic change (see below).…”
Section: Endemismmentioning
confidence: 99%
“…In a large-scale survey of outdoor dust samples, Grantham et al (2015) found evidence for geographic endemism for many dust fungi. Specifically, they obtained the ITS-1 sequences directly through high-throughput metabarcoding from nearly 1000 dust samples collected from the top edges of doors opening to the outside environment, from across the continental US.…”
Section: Metabarcoding Indoor Dust and Air Samplesmentioning
confidence: 99%
“…Many of these taxa exhibited a high degree of geographic specificity, with 72% of the observed OTUs found in less than 10 dust samples. Based on the geographic endemism in dust fungal diversity, the authors developed a statistical learning algorithm via discriminant analysis that allowed correct identification of dust samples to within a few hundred kilometers of their geographic origin with high probability (Grantham et al 2015). This work also opened up a new approach to forensic biology where fungal barcodes could be used to identify the potential origins of dust samples found on a variety of objects.…”
Section: Metabarcoding Indoor Dust and Air Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…temperature, humidity) that select for certain taxa in certain regions. We expect that indoor fungi will exhibit particularly strong variability across geographical regions, given that most fungal taxa found indoors come from outside the home [27] and the fungi found in outdoor air can exhibit a high degree of geographical endemism [31,32]. Yet, the biogeography of indoor microbial life remains largely unstudied with the exception of a single study of 72 buildings, in which strong effects of climate were found on indoor fungal taxa [25].…”
Section: Introductionmentioning
confidence: 99%